Bilirubin induces loss of membrane lipids and exposure of phosphatidylserine in human erythrocytes - Brito, MA (2015)
Unconjugated bilirubin increasingly binds to erythrocytes as the bilirubin-to-albumin molar ratio exceeds unity, leading to toxic manifestations that can culminate in cell lysis. Our previous studies showed that bilirubin induces the release of lipids fro